MODEL PERTUMBUHAN BIOMASSA RUMPUT LAUT GRACILLARIA DENGAN CARRYING CAPACITY BERGANTUNG WAKTU - Zullaikah, Zullaikah; sutimin, sutimin (MATEMATIKA, 2008)
In this journal, we will discuss concerning with a dynamical model of growth of seaweed biomass. The model will be applied in the biomass growth of GracillariaÂ seaweed. The dynamical model is developed from the simple logistic model by considering the influence of resource absorption of ecosystem which support the environment. We assume that the resource absorption changes time dependent. By this assume, we include that the carrying capacity as function of time. To analyze the stability of the model equation, here we use the linearization method of the expansion series Â